A CONCEPTUAL STUDY OF SHIRODHARA IN THE MANAGEMENT OF SHIRAHSHOOLA (AYUSHDHARA, 2017)
One of the challenging and very common conditions in current modern era is headache. At present all age groups from young to old are affected by it. headache is a very commonly occurring condition in our today’s practice. Modern medications do not help much as analgesics have their own aftereffects. Hence it is the need of time to bring forward such treatment options which do not cause much side-effect and give positive results in the management of headache with minimal use of oral drugs. Among the different treatment described in Ayurveda, Shiro Dhara is one of the commonly practiced procedures in the disorders of head & scalp. It can be used as preventive measure in different stressful conditions. Shirahshoola is a disease as described in Ayurveda which involves all kinds of headache. In this paper, I want to explain, different types of shirahshoolaand there management which describe in Ayurveda very well and one of the most practically used procedure shirodharawhich is very effective in headache.